A Case Study in the Application of an Agent-Based Approach in the Formulation of Policies for UK Transport Emission Reduction - TAEIHAGH, Araz (Institutional Knowledge at Singapore Management University, 2010)
The increased complexity in our socio-economical systems requires the development of new tools to support a better understanding of the intricacies involved in addressing problems associated with such systems. We believe that by introducing a systematic approach for exploring alternative policies we can improve the decomposition of these problems, decrease the required time for analysis and formulate more effective polices. A case in policy formulation and analysis in the transport sector for achieving CO2 emission targets in the UK is presented; this solution is based on a previously proposed framework (Taeihagh et al., 2009a). The results obtained from the analysis of policy measures and their relations are used in the formulation of policy alternatives (packages and clusters) through the application of agent-based modelling. The results have the potential to further promote the use of computational approaches in the formulation of polices through the development of software systems that can support the design of policies for different sectors and geographical scopes.